ANALYZING THE CLASSIC METHODS OF ORGANIZING THE ADMINISTRATION ACCOUNTACY USED IN THE CARBONIFEROUS MINING INDUSTRY - PALIU-POPA Lucia; DINA Ionela-Claudia (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2009)
Information regarding production costs occupy a central slot, determined by their implications regarding the present and future evolution of a company. The value of information regarding the cost of production justifies its use both in decisions regarding the current activity and in the company’s future strategy. The efficient organization of economic activity in the carboniferous mining industry imposes a constant improvement of management methods, which also implies a reconsideration of administration accountancy methods and cost control, which have to become capable of offering information that can be compatible to the requirements for an efficient management of the production process, in a market economy.